Estimation and Statistical Test in Bivariate Binary Probit Model - Vita Ratnasari; Purhadi Purhadi; Ismaini Ismaini; Suhartono Suhartono (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2011)
One of the models that can be used to analyze two binary response variables data is bivariate binary probit model. This paper tried to estimate the parameters of bivariate binary probit model using Maximum Likelihood Estimationmethod, whereastoget the statistical test using Maximum Likelihood Ratio Test method.